Hubungan Komunikasi Interpersonal Ibu dan Remaja dengan Perilaku Cyberbullying pada Remaja - Ade Liana; Nofha Rina (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
Interpersonal communication is an effective interaction to be carried out between two individuals, one of which is in the family environment between mothers and adolescents. This study aims to determine the relationship between mother and adolescent interpersonal communication with cyberbullying behavior in adolescents. This research is quantitative research using correlation analysis as a data analysis technique. The subjects of this study were students of SMA Yadika 6, Pondok Aren, with a total of 101 students. Collecting data using a questionnaire using a random sampling technique. The results showed that the significance value of 0.200 > 0.05 means that the data is normally distributed. The correlation coefficient results show a sig value of 0.657. The results of this research hypothesis are the t-count value of 8.670 and a significance value of 0.000 <0.05. This means that the proposed hypothesis is accepted, or it can be interpreted that interpersonal communication between mothers and adolescents with cyberbullying behavior in adolescents has a significant relationship.